The role of identity in the development of senior leader expertise: a constructive-developmental perspective - Popkova, Oxana (Cranfield University, 2012)
Background: The multi-billion dollar leadership development industry relies on practitioner approaches that in mainstream prescribe the content view of leadership pipeline development – recruiting in traits and attributes, and training up skills and behaviours. This approach is not delivering the expected results. However, a reliable evidence-based process approach to leader development has not yet emerged. Purpose: This study addresses the insufficiency of the current theory and evidence relating the mechanisms of development of senior leader expertise. Methodology: The study relies on the systematic review method (Tranfield, Denyer & Smart, 2003) to qualitatively analyse the literature on leader expertise and the role of identity in leader development from constructive-developmental perspective. Findings: A review of literature on leader expertise explored the specifics of the research gap in the understanding of the logic, the factors and the process behind the development of senior leader expertise. Although recent theories of leader expertise indeed proposed that leader identity provides a crucial knowledge structure around which leader expertise evolves, as well as an impetus for leader expertise development, virtually no research exists to back up this idea. However, research associated with the constructive-developmental theory, an adult development perspective largely unrelated to the leader expertise enquiry, provides some evidence of the association between identity and developmental outcomes that may be used as the first pass at validating the identity propositions of the leader expertise theorists. This review of leader expertise and identity from constructive-developmental perspective helped me formulate a framework for analysis of leader expertise from identity perspective. This framework may be used in my future PhD research as a starting point for modelling of identity processes in the development of senior leader expertise.